2007
DOI: 10.1007/s00422-007-0148-2
|View full text |Cite
|
Sign up to set email alerts
|

Spike-timing-dependent plasticity for neurons with recurrent connections

Abstract: The dynamics of the learning equation, which describes the evolution of the synaptic weights, is derived in the situation where the network contains recurrent connections. The derivation is carried out for the Poisson neuron model. The spiking-rates of the recurrently connected neurons and their cross-correlations are determined self- consistently as a function of the external synaptic inputs. The solution of the learning equation is illustrated by the analysis of the particular case in which there is no exter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
126
2

Year Published

2008
2008
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(132 citation statements)
references
References 14 publications
4
126
2
Order By: Relevance
“…We investigate the dynamics of recurrently connected linear Poisson neurons excited by steady external pulse trains with a correlation structure [1,2]. The input synaptic weights are modified in accordance to "additive" STDP that relies upon both rate-based and pairwise-correlationbased changes [1,2]; the recurrent weights are kept fixed.…”
Section: Models and Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…We investigate the dynamics of recurrently connected linear Poisson neurons excited by steady external pulse trains with a correlation structure [1,2]. The input synaptic weights are modified in accordance to "additive" STDP that relies upon both rate-based and pairwise-correlationbased changes [1,2]; the recurrent weights are kept fixed.…”
Section: Models and Methodsmentioning
confidence: 99%
“…The input synaptic weights are modified in accordance to "additive" STDP that relies upon both rate-based and pairwise-correlationbased changes [1,2]; the recurrent weights are kept fixed. The network dynamics (evolution of the firing rates, of the correlations, and of the weights) is described by a dynamical system [2].…”
Section: Models and Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…: [8]) which have proven to replicate the biology. Burkitt et al [6] found a mathematical and statistical description of the standard STDP rule.…”
Section: Introductionmentioning
confidence: 99%